Teacher Development in Technology-Enhanced Language Teaching - Son, Jeong-Bae (Springer International Publishing, 2018)
'A well-crafted book in which a strong base in theory and research informs a rich collection of practical options for those navigating the complex world of language teacher education for the 21st century.' - Philip Hubbard, Stanford University, USA 'This book looks at educating teachers in the use of computer-assisted language learning (CALL) from a novel and interesting perspective. The contents are based on a thorough familiarity with research into teacher development for CALL, combined with interesting, down-to-earth tasks for practice in, and reflection on, the use of technology for language learning. The list of resources of various kinds is reason enough in itself for readers from a wide variety of backgrounds to buy the book, which should feature on a reading list for any training course for language teachers.'" - Scott Windeatt, Newcastle University, UK 'The author's experience is evident throughout and the practical tips, founded on relevant research, are invaluable to teachers regardless of how little or how much experience they have with technology in their teaching and learning contexts.' - Glenn Stockwell, Waseda University, Japan This book explores language teacher development in computer-assisted language learning (CALL) environments and discusses approaches, tasks and resources that can guide language teachers to develop their skills and strategies for technology-enhanced language teaching (TELT). It looks at key aspects of CALL in terms of pedagogy and technology and proposes a model of CALL teacher development, which incorporates essential elements of teacher learning in CALL. Further, the author presents practical tasks and tips on how to develop knowledge and skills for the use of digital technologies in language teaching and suggests ideas to improve language teacher training and development. Jeong-Bae Son is Associate Professor in Applied Linguistics & TESOL at the University of Southern Queensland, Australia. His areas of specialisation are computer-assisted language learning and language teacher education. He is the President of the Asia-Pacific Association for Computer-Assisted Language Learning (APACALL) and Editor of the APACALL Book Series.